Problematika Pembelajaran Daring Mata Pelajaran PAI di Masa Covid-19 - Fitriyana Fitriyana; Firda Ayu Wahyuni (Institut Dirosat Islamiyah Al-Amien Prenduan, 2021)
In min-2020 the whole word was shocked by the existance of covid-19, this covid had a huge impact in the word of education, including learning Islamic Relegion Education, so that is was trasferred from being face to face to online system PJJ. Islamic Relegion Education plays an important role for students because basically the purpose of Islamic Relegion Education is to increase the faith of studen, and undrestanding of studen so that they become faithfull and devoted people and have noble character in their lives, society, nation and country even tought the situation is still a covid pandemic-19. The purpose of this study is to determine the problem of students and the efforts of parent od students in overcroming problems that occur in students in the learning procces online or PJJ. This research uses qualitative field research methods in which a researcer goes directly to the field observing and data collection techniques used, namely by observation and interviews with students and parent of students in order to find out the problems of online learning experinced by students. In a pandemic situation that requires online learning for students, of course, they experience problems such as what happened in Totosan, Batang Batang District. As for the problems that are often faced, namely learning is less than optimal and confusive, lac of understanding of PAI material by student and parents of students, lack of cellphone availability and poor network connection and busy parents of students when online learning begins. So that of students need efforts to evercome the problems that occur, such as continuing to provide support and guedance as much as possible to students as well as holding peer group learning guided directly by parentsof student who understand better.